2016
DOI: 10.1590/s1677-5538.ibju.2015.0116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ejaculation on Serum Prostate-Specific Antigen concentration

Abstract: Purpose:To evaluate the effect of ejaculation on serum prostate-specific antigen (PSA) concentrations in patients with lower urinary tract symptom (LUTS).Materials and Methods Our study includes 98 men (62 study and 36 control). After three days of sexual abstinence, blood samples were drawn for the measurement of baseline PSA levels. Then the patients were told to ejaculate. One, 5, 24 and 72 hours after ejaculation, serum total (tPSA), free (fPSA) and complexed PSA (cPSA) levels were measured. Serum PSA samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…Also in human medicine, ejaculation has been claimed to be one of the factors affecting PSA values, and its effect has been evaluated in several studies, reporting at first conflicting results with increased, unchanged, or decreased PSA concentrations after ejaculation [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Nevertheless, in works reporting decreased or unchanged PSA concentrations, sampling time intervals after ejaculation were too long (1 to 7 days after ejaculation) to detect early PSA elevations, which are instead observed during the very first hours [21]. Recently, it was definitively stated that the serum concentration of PSA increases at 1 h after ejaculation and returns to baseline values at 24 h [20,21,29] in 92% of patients [27].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Also in human medicine, ejaculation has been claimed to be one of the factors affecting PSA values, and its effect has been evaluated in several studies, reporting at first conflicting results with increased, unchanged, or decreased PSA concentrations after ejaculation [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Nevertheless, in works reporting decreased or unchanged PSA concentrations, sampling time intervals after ejaculation were too long (1 to 7 days after ejaculation) to detect early PSA elevations, which are instead observed during the very first hours [21]. Recently, it was definitively stated that the serum concentration of PSA increases at 1 h after ejaculation and returns to baseline values at 24 h [20,21,29] in 92% of patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in works reporting decreased or unchanged PSA concentrations, sampling time intervals after ejaculation were too long (1 to 7 days after ejaculation) to detect early PSA elevations, which are instead observed during the very first hours [21]. Recently, it was definitively stated that the serum concentration of PSA increases at 1 h after ejaculation and returns to baseline values at 24 h [20,21,29] in 92% of patients [27]. The present study demonstrated that 24 h after ejaculation, increased serum CPSE came back to basal values in 90% of tested animals, following a trend similar to that reported for PSA in human medicine [20,21,27,29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations